EDUCATION DILEMMA AND CHALLENGES OF THE CREATIVE INDUSTRY CRAFTSMEN IN PLACED PURWAKARTA - Achmad Siswanto; Nika Arundina Lusty; Abdul Hakim Syafi’i (LPPM Universitas Negeri Jakarta, 2023)
This study aims to describe the challenges and dilemmas in the gerabah craft business as a sub-sector creative industry. This study uses a qualitative approach with a case study method as a strategy of inquiry—primary data collection by in-depth interviews and observations. Meanwhile, secondary data was collected through document studies and analyzed using qualitative and in-depth literature studies. The results of this study indicate that pottery artisans in Kampung Lio, Kecamatan Plered, and Purwakarta have the opportunity to reach the digital market and develop a home industry which can be projected to become a pottery tourism village. However, these opportunities are difficult to reach because they are faced with several challenges, namely low level of education and surrender mentality, and limited financial capital make it difficult for them to develop.